2016
DOI: 10.1039/c6sc00429f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dye regeneration kinetics in dichromophoric porphyrin–carbazole triphenylamine dyes influenced by more exposed radical cation orbitals

Abstract: Dye regeneration kinetics is enhanced by five times in a di-chromophoric porphyrin dye by attaching tridimensionally enlarged electron donor moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In 2016, we showed that TPA – carbazole units attached to porphyrin molecules on TiO 2 enhanced the electron transfer rate by up to five times at the same driving force (see Figure 16). [5b] In this system, sub‐nanosecond hole transfer was observed from the porphyrin cation radical to the TPA‐carbazole donor unit. The regeneration rates probed at wavelengths corresponding to the TPA‐carbazole cation radical was five times faster than at wavelengths corresponding to the porphyrin cation radical, which was explained by the larger interface of the carbazole‐TPA towards the electrolyte.…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 89%
See 1 more Smart Citation
“…In 2016, we showed that TPA – carbazole units attached to porphyrin molecules on TiO 2 enhanced the electron transfer rate by up to five times at the same driving force (see Figure 16). [5b] In this system, sub‐nanosecond hole transfer was observed from the porphyrin cation radical to the TPA‐carbazole donor unit. The regeneration rates probed at wavelengths corresponding to the TPA‐carbazole cation radical was five times faster than at wavelengths corresponding to the porphyrin cation radical, which was explained by the larger interface of the carbazole‐TPA towards the electrolyte.…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 89%
“… Chemical structures of the porphyrin dye (Por), the TPA‐carbazole moiety (Cb‐TPA), and the extended Por with the moiety (Por‐(Cb‐TPA)) [5b] . Reproduced from Ref.…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 99%
“…Carbazole groups possess large similarity to the DPA, but with more rigid configuration (Zhao et al, 2016 ). Considering the “ring fusion” effect, one can expect a lower HOMO energy level of carbazole conjugated porphyrin compared to the DPA porphyrin (Qi et al, 2015 ).…”
Section: The Development Of Porphyrins For Solar Cell Applicationmentioning
confidence: 99%
“…One of the interesting aspects of the multi-chromophoric design is that the electronic communication between the chromophores can be inhibited by a twisted three-dimensional structure, weakening the dispersion forces (polarizability of the molecule) and elongating the electron lifetime [ 9 ]. Furthermore, intramolecular hole transfer between the porphyrin and the side chain chromophore can lead to faster dye regeneration rate at the TiO 2 /dye/electrolyte interface without increased driving force for the electron transfer reaction [ 12 ]. However, the PCEs of DSSCs using multi-chromophoric porphyrin dyes are often lower than those of the best single porphyrin or porphyrin/organic dye co-sensitized solar cell approaches.…”
Section: Introductionmentioning
confidence: 99%